Mediation in the teaching of addition and subtraction in Peru and Colombia - Santana Espitia, Ana Cristina (2022)
This study investigates three facets of teacher mediation: a) The sensitivity to the needs of the student with difficulty (perceived difficulty), b) The way to organize activities and experiences that encourage learning and c) The ability to institute tasks with diverse levels of complexity (instituted difficulty). The Test for Assessment of Instituted Difficulty in Situations of Addition and Subtraction (DISAS) (Santana & Herrera, 2017) was applied to 20 Peruvian and 20 Colombian teachers from 1st to 5th grade of elementary school, who described their way of orienting students with difficulty to add and subtract. The results obtained suggest that the cultural environment is important in the organization of the teacher’s activity when teaching these operations.